Habitual responding for alcohol depends upon both AMPA and D2 receptor signaling in the dorsolateral striatum - Corbit, Laura H.; Nie, Hong; Janak, Patricia H. (Frontiers in Behavioral Neuroscience, 2014)
Chronic alcohol self-administration leads to alcohol-seeking behavior that is habitual and insensitive to changes in the value of the earned alcohol. Such behavior has been shown to rely on the dorsolateral region of the striatum in rats but the specific pharmacological control of output from this region is not yet understood. In the following experiments rats were trained to self-administer unsweetened 10% (v/v) ethanol in daily sessions for eight weeks prior to testing for sensitivity to outcome devaluation. We examined the role of glutamatergic AMPA-receptor activation by testing the effects of the antagonist NBQX (0.3 and 1.0 µg/µl) infused specifically into the dorsolateral striatum before devaluation testing. In a separate group of rats we examined the role of dopaminergic D2-receptor activation using the D2-receptor antagonist raclopride (0.2 and 1.0 µg/µl) infused into the dorsolateral striatum before devaluation testing. Following control (saline) infusions rats’ lever-press performance was insensitive to devaluation of ethanol thus showing evidence of habitual responding. NBQX and racolpride each restored goal-directed control of responding at doses that did not impair overall lever-press rates. These data demonstrate that expression of habitual alcohol seeking relies on glutamatergic inputs to the DLS and D2 receptors within the DLS.